Opportunities and challenges of pain-related myocardial ischemia-reperfusion injury - Jiang, Wenhua; Yin, Yue; Gu, Xiaoming; Zhang, Zihui; Ma, Heng (Frontiers in Physiology, 2022)
The global prevalence of pain is as high as 53%. Pain is not an independent pathophysiological condition and associated with a high impact on elevated disability and organs dysfunction. Several lines of evidence suggested the associations of pain with cardiovascular diseases, especially myocardial ischemia reperfusion (I/R) injury, while the role of pain in I/R injury and related mechanisms are not yet comprehensively assessed. In this review, we attempted to explore the role of pain in myocardial I/R injury. We provide detailed insights into the construction of different pain models, and the dual role of pain in myocardial I/R injury, further summarize the underlying mechanisms in pain-related myocardial I/R injury. In addition, we discuss the challenges in the future study on myocardial I/R injury in patient suffering from pain.